Hak-Hak Asasi Manusia dalam Hukum Islam - Hamidah, Tutik (el Harakah: Jurnal Budaya Islam, 2000)
Human rights objectively aim noble. It grants basic rights to human beings without distinction of origin, race, color, sex, language or religion. The concept of human rights in maqasid al syariah is Islamic sharia is prescribed in order to protect the human benefit by protecting the interests, safety and welfare of human beings both in life in the world and in the hereafter. The fundamental problem, if Islamic law is confronted with human rights is at least in family law. There arose some offers of methods of understanding nas in order to respond to human development. A verse of qatb'i is by analyzing a number of verses so that a unified understanding of the verses can be obtained. The collaboration of some of these verses shows that the understanding contained therein is definite and undeniable. then the tension in Islamic law, especially allegations of discrimination against women and non-Muslims can be avoided without any need to have allegedly left the Qur'anic verses. Hak-hak Asasi manusia secara obyektif bertujuan mulia. la memberi hak-hak dasar kepada manusia tanpa membedakan asal-usulnya, baik ras, warna kulit, jenis kelamin, bahasa maupun agama. Konsep HAM dalam maqasid al syariah yaitu syariah Islam disyariatkan dalam rangka melindungi kemaslahatan manusia dengan melindungi kepentingan, keselamatan dan kesejahteraan manusia baik dalam hidup di dunia maupun di akhirat. Problem yang mendasar, jika hukum Islam dihadapkan kepada HAM paling sedikit adalah pada hukum keluarga. Muncullah beberapa tawaran metode memahami nas dalam upaya merespon perkembangan kemanusiaan. Suatu ayat qatb 'i adalah dengan menganalisis sejumlah ayat sehingga bisa diperoleh suatu pengertian yang searah dari ayat-ayat tersebut. Kolaborasi sejumlah ayat tersebut menunjukkan bahwa pengertian yang terkandung di dalamnya bersifat pasti dan tak terbantah. maka ketegangan dalam Hukum Islam, khususnya tuduhan diskriminasi terhadap wanita dan non-muslim bisa dihindarkan tanpa perlu ada tuduhan telah meninggalkan ayat-ayat al quran.